Influence of early life exposure to social disadvantages on deliberate self-harm (DSH) among children of parents with mental health disorders. (2017) - Hu, Nan; Taylor, Catherine; Glauert, Rebecca; Li, Jianghong; Wong, Janice
No abstract available